(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This paper present the space as a structuring element of staging, based on the project developed by the theater group mundana companhia in Na Selva das Cidades - Em Obras #ocupasp (2014-2017). From this perspective arises the critical power of theatrical practices that understand scenic spatiality not only as an aesthetic determination, but as a social space. Thus, theater becomes a means of unveiling and criticizing issues that speak of the current urban condition of São Paulo.